An introduction to the Bible - Rogerson, J. W. (John William), 1935-2018 (Equinox Publishing, 2012)
The Bible is one of the most influential and profound texts in human history - it is disturbing, unconventional, and never content with the world as it is. This classic introduction presents a concise and accessible guide to all aspects of biblical study: the nature and purpose of the Bible; how biblical writers wrote; the making of both Old and New Testaments; the making of the Apocrypha; what was left out and what kept in the Bible and why; and how the Bible has been shaped by and continues to shape religion, culture and politics. Completely revised and updated - and considerably extended.